Temporal lobe epilepsy with GAD antibodies: neurons killed by T cells not by complement membrane attack complex - Troscher, Anna R.; Mair, Katharina M.; De Juan, Laia Verdu; Koeck, Ulrike; Steinmaurer, Anja; Baier, Hartmut; Becker, Albert; Blümcke, Ingmar; Finzel, Martin; Geis, Christian; Hoftberger, Romana; Mawrin, Christian; et al. (Brain, 2022)
Troscher et al. show that in patients with GAD65 antibody-associated temporal lobe epilepsy, cytotoxic T cells attack and kill neurons and are responsible for the early neuronal loss. Immunological treatment within the first few years may thus be necessary to prevent irreversible hippocampal damage.
CRIS-Team WoS Importer:2023-03-10